Pengaruh Volume dan Jenis Media Tanam pada Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa) dalam Teknologi Hidroponik Sistem Terapung - Anas D. Susila; Yuni Koerniawati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
The objective of this study was to find out the effect of volume and source of growth media and lettuce growth and yield in Deep Pool Growing System (DPGS). The study was conducted from September to December 2003 at Deep Pool Growing System facility, Danasworo Hydro - Garden Ciapus, Bogor. The Study was arranged in randomized completely block design with two factors. First factor was volume of growth media ( 20 cm³ and 110 cm³). The second factor was source of growth media (synthetic foam, cocodust, rice-husk + OSF and rice-husk + cocodust). Medium volume of  20 cm³ with rockwool was used as a check. Nutrient compotion of the solution was as follows (ppm): Ca 117, Mg 24, K 210, NH4 25, NO3 233, SO4 113, and PO4 60, Fe 2.14, B 1.2, Zn 0.26, Cu 0.048, Mn 0.18, and Mo 0.046. Medium volume of 20 cm³ with synthetic foam obtained the best yield for all parameters. Therefore, this treatment could replace rockwool as medium for lettuce production in DPGS.   Key words : Deep Pool Growing System, hydroponics, growth medium